Current transformers transient response modelling using electromagnetic transient program (EMTP) - Chuthi, Noel Nelson Stima (Department of Electrical Engineering, 2016)
The subject of this thesis is Current Transformer Transient response study using an electromagnetic Transient program (EMTP). Current transformers are considered eyes for power system protection. Behaviours of protection systems depend largely on information fed to them by instrument transformers. Ferromagnetic current transformers have for many years provided practical method of current measurement, however there are limitations associated with current transformer operation:- notably, difficult in maintaining accuracy over the full range of operating conditions, and most particularly current transformers tendency to suffer saturation of iron core during severe faults, with accompanying severe ratio or loss of output. These limitations might lead to mal operation of protective relays due to distorted inputs from current transformers particularly in transient periods. This thesis involved studying the behaviour of current transformers in both steady state and transient periods. An emphasis being put on transient periods which are very crucial in behaviour of current transformers because transformation errors are greatest in these periods. Errors in current transformer transformation might affect operation of entire protection schemes. Maloperation of current transformers in transient periods have very bad effect on relay co-ordination and worst condition might be failure of protection scheme operation altogether. Over the past decades engineers have been trying to develop a current transformer model that would represent a current transformer well in transient periods. It has proved to be rather difficult to come up with a single detailed model that would satisfy all possible conditions. This is due to non-linearity of magnetising curve and saturation effects of current transformer iron cores. The author has considered different current transformer models with their merits and demerits being highlighted. It has been shown that different current transformer models have to be used when considering different operating conditions of a current transformer in a power system. ATP-EMTP an Electromagnetic Transient Program was developed in the sixties for the study of electromagnetic transients in power systems. It has proved to be a very useful tool in this regard. The program development is still going on today to accommodate a wide application in power systems. Several components have been developed to represent different components in a power system. It is only recently that there has been a growing interest to include modelling of protective equipment. This has been accelerated by the inclusion of MODELS in the EMTP program. This thesis explores the effect of transients taking into account different conditions like transient fault currents, effects of high frequency waves and surges. Effects of different types of burdens on current transformers were explored as well. Due to limitations of EMTP, simulation results are only applicable to current transformers with ARMCO M4 oriented steel with ungapped cores. The author arrived at several conclusions. The most important conclusion is that mal operation of protective relays due to current transformer saturation can be avoided easily if proper current transformer selection is given priority in power protection design. EMTP package proved to be very useful and handy when studying transients though one has to be careful with numerical oscillations which might be present during simulations. Problems of numerical oscillations have been discussed under current transformer simulation tools.